Research of the Electric Power Conversion in Wind Turbines with the Aerodynamic Multiplication - Alekseevskiy D.G.; Andrienko P.D.; Nemykina O.V. (Problems of the Regional Energetics, 2019)
The paper deals with the research of busbar power losses depending on electrical equipment installation and the dynamic change of the generated power of a wind turbine with the aerodynamic multiplication. The analysis of the electricity conversion electromechanical system is carried out on the example of the first Ukrainian pilot wind turbine with the aerodynamic multiplication of the TG-1000 type. The aim of the article is analytic method creation of analysis of power relative losses in busbars of electrical equipment depend on its arrangement, as well as the research of electromagnetic processes in the electromechanical system depend on the wind flow speed at the height axis of the turbogenerators setted on the blades of the wind wheel (WW) turbine by computer modelling method. This aim achieves by the rectifiers series connection and their location changing (generator clips), which allows the DC energy transfer inside the wind turbine. The research results have showed that power losses reduce in busbars and lead to increase wind turbine efficiency and decrease cable consumption. Electromagnet processes modelling of visual block model have evidenced the adequacy of the assumptions in the determination of the power losses. It has been obtained that the wind flow speed irregularity at the height axis of the turbogenerator and steering angle between turbogenerator axis and wind wheel rotation plane provokes the power generation variances, which pulse according to wind wheel rotation speed. In addition, balanced current of the circuit has provided the symmetrizing amplitudes of the power generator.